KOMODIFIKASI PEREMPUAN DALAM RUBRIK JELITA SURAT KABAR RIAU POS - Fuji Rahayu; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Jelita Rubrik of Riau Pos Newspaper displays information related to the hobbies, achievments and contributions of young women in Riau Province. The rubric also provides profile and photographs of objects that support the text. In writing, the writer tends to describe and amphasize the women physical aspect.  Rubric Jelita is published in eight editions, and five of them raise the topic of the world of beauty. The study aims to determine women representation in the subject-object position, women representation in thewriter-reader position, and the commodification proccess in the Rubrc Jelita.This study uses a qualitative method with the Sara Mills Discourse Analysis’s which focuses on feminism, and how actors was seen in text, and also  Vincent Mosco’s Commodity Theory which related to proccess of commodification in Rubric Jelita. The paper examined using the data consist of documentation, observation, and interviewers of 6 (six) peoples. The subject in this study is Riau Pos who became the informant, with 5 (five) news as the analysist unit. This study uses two data validity checking techniques, namely triangulation source and triangulation method.The result showes that, First, women became the object of all discourses, and found three ouf of five discourses subject positioned themselves as women, and two discourses positioned themself as men. From the whole discourse, the subject seems to give the object an opportunity to present herself. Second, subject-object positioning also influences the position of writer-reader. Third, the visible commodification of content is the inspiring story of women about their contributions and achievments, especially in the pageant world. the writer  involved is quite careful in writing and gives the object the opportunity to describe herself. In the commodification of audience, there is a soft selling and offer of household advertisements on the Rubric Jelita. Keyword: Commodification, Feminism, Sara Mills, Riau Pos Newspaper